1990
DOI: 10.1002/cyto.990110808
|View full text |Cite
|
Sign up to set email alerts
|

Cytophotometric analysis of cervical intraepithelial neoplasia grade III, with and without synchronous invasive squamous cell carcinoma

Abstract: Cytophotometric analysis was performed in nuclei retrieved from paraffinembedded cervical tissue from 57 cases of CIN 111. CIN 111 lesions of patients without invasive squamous cell carcinoma (N = 37) were regarded to represent a mixture of progressive and nonprogressive lesions. The CIN 111 lesions of patients with a synchronous invasive squamous cell carcinoma (N = 20) were regarded as representing truly progressive precursor lesions (C1N.INV). Twenty-one photometric features describing geometrical, density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The aneuploid LSIL probably belongs to the group that has the ability to progress to biopsy proven CINIII/CIS. 7 It has been shown that in up to 30% of cases of LSIL, a follow-up biopsy will show CINIII/CIS. 15,4 The predictive positive value of DNA aneuploidy to predict those cases of the diagnostic Group IIID of the Munich II classification that will progress to CINIII/CIS was only 42%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aneuploid LSIL probably belongs to the group that has the ability to progress to biopsy proven CINIII/CIS. 7 It has been shown that in up to 30% of cases of LSIL, a follow-up biopsy will show CINIII/CIS. 15,4 The predictive positive value of DNA aneuploidy to predict those cases of the diagnostic Group IIID of the Munich II classification that will progress to CINIII/CIS was only 42%.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]12,16,17,[23][24][25]27, DNA aneuploidy has been regarded as an objective marker for progressive CIN. 7,33,60 DNA cytometry can be done on a routine basis using PC-based commercially available cytometers, which makes the diagnosis of DNA ploidy easy. 25 Research indicates that HSIL lesions are probably induced by oncogenic human papilloma viruses (HPVs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, they made us disqualify several subjects' material (61.1%) for having a totally irregular distribution of chromogen results in diverse nucleus cells and a major intensity in a specific place, perhaps, due to the different fixing agents during impregnation method (Hanselaar et al, 1992). The usage of different fixing agents with different fixation methods shows some varieties about chromogen intensity in the ionic hydrogen concentration and the hydrolise time in Feulgen's reaction (Böhm;Böhm et al, 1968) that could interfere in the condensation of chromatin's spatial distribution and, apart from tracking the DNA, does the same with proteins (Stedman & Stedman, 1950), Umayahara et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…9 A particularly useful ancillary study in cervical cytology would be DNA profiling, as performed earlier. 13,18,20,26 The process of destaining these conventional smears and restaining with the Feulgenthionin procedure, however, leads to unpredictable losses in stainable content according to some investigators. 1 Other investigators have resorted to disaggregation of nuclei from subsequent cervical biopsies in order to investigate DNA ploidy of cervical lesions.…”
mentioning
confidence: 99%